City Hall Clock - O'Donoghue, Florence, 1895-1967 (1920)
Close-up of city hall clock with bullet holes and broken glass panes.
Keywords: City Hall; Ireland -- History -- War of Independence, 1919-1921; Photographic prints -- Irish -- 1910-1920